Diarrhoeal diseases and the global health agenda : measuring and changing priority - Bump, Jesse B. (2013)
Studies the history of the control of diarrhoeal diseases (CDD). Measures CDD priority on the global health agenda over time, using four kinds of indicators, and then proposes strategies for changing its priority to reinvigorate efforts to save more children from DD.